The Father's Storytelling Approach in Improving Children's Vocabulary Using Anime - Pramudana Ihsan; Annisa Tiara Syafitri (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
This research is based on the implementation of anime for children's vocabulary mastery by their father’s storytelling. The researcher describes the impact of teaching English using vocabulary through anime reading materials using several vocabulary teaching techniques. The subject of this research is a father who works from home and his son who is studying English, amounting to 10 couples. This methodology has several advantages including classroom action research which consists of planning and taking surveys through online data collection. Data were analyzed with qualitative data. After analyzing, the authors concluded that the learning process using cartoons had good results. This can be seen from the increase in children's vocabulary and increased English language skills. The results were particularly good in the child's increased memory and attractiveness to read. The vocabulary of 85% of children is also increased and 15% can implement a few words in daily conversation. During the teaching and learning process, almost 90% of children feel comfortable, active, and excited. Research has shown that teaching using animated cartoons can increase students' vocabulary mastery.